The metaphorical expression of Nature in Jørn Utzon's design for the Sydney Opera House. Issue 4 (12th May 2016) - Chen-Yu, Chiu; Goad, Philip; Myers, Peter
Abstract : Both before and after his forced resignation from the charge of the Sydney Opera House (1956–66)in 1966, Danish Architect Jørn Utzon (1918–2008) has cited Chinese architecture as one of the most important inspirational sources of his unfinished masterpiece. However, the significance of Chinese building culture has largely been overlooked in historical accounts of Utzon's Opera House design. This is despite ample evidences suggesting several direct analogies of Chinese architecture in Utzon's design proposals. The evidence also indicates that one of the key Chinese sources for Utzon comes from the written works of Finland-born and Sweden-based art historian Osvald Sirén 喜龍仁 (1879–1966). Accordingly, this paper aims to identify Utzon's perception of Chinese architecture from Sirén's interpretation of this subject, and Utzon's eventual reinterpretation of this notion in his design of the Sydney Opera House. The article poses four questions. First, what were the socio-political contexts both of Sirén and Utzon's approach to Chinese architecture? Second, how did Sirén interpret Chinese architecture in his scholarly work? Third, what was the interrelationship between Sirén and Utzon? And fourth, how did Utzon reinterpret Sirén's concept in his design for the Sydney Opera House? To respond to these questions, the authors surveyed the literature associated with Sirén and Utzon, reviewed their private collections, and undertook interviews with their friends, colleagues and followers. On this basis, the authors constructed a series of ideological analogies between Sirén and Utzon's work, with particular emphasis on Utzon's design for the Sydney Opera House.